Analysis of Pencak Silat Techniques For The Winner of The Men's 70-75 Kg Competition Category at The 2023 Sea Games - Wildan; Hadi, Hadi; Yudhistira, Dewangga (Journal of Sport Science and Fitness, 2024)
Pencak silat is now developing into a competitive sport that is recognized worldwide. The need to analyze pencak silat techniques, this study aims to analyze the pencak silat techniques used by the winners of the men's 70-75 kg class competition category in the 2023 SEA Games. The research method used in this study is quantitative descriptive, by making observations to find out the techniques of kicks, punches, and slams through the sea games competition in the competition category as the winner of a body weight of 70-75 kg. The participant in this study was the winner of the 70-75 kg class F competition category, namely Iqbal Chandra. Based on the results of the above analysis, it can be concluded that the winner of the 70-75 kg Sea Games class F competition category Iqbal Chandra in the preliminary round is dominant using techniques namely 32% punches and 21% catches, in the semi-final round Iqbal Chandra is dominant using 28% punch techniques, 17% T kicks, and 17% falls with a catch process, and in the final round Iqbal Chandra is dominant using 22% sickle kick techniques,  front kicks/A 17%, and falls with a catch process 17%.